Color Linguistics: Khanty riddles - Andreeva, Lyudmila; Khudobina, Olga; Moldanova, Tatyana; Miryugina, Nataliya (SHS Web of Conferences, 2022)
From the point of view of physics and physiology, the perception of color should be the same by all people, but the process and associations connected with it have historical and cultural determinants in different nations. The conceptual apparatus of color linguistics is studied in different scientific studies and from different points of view. The material of this study comprises riddles extracted from Khanty folklore by the method of continuous sampling, as well as scientific literature on the descriptionof color words. A common way of creating riddle metaphors is color matching. Therefore, exploring color words in the Khanty riddles allows us to reveal the cognitive, pragmatic and cultural factors of language functioning. The present research highlights the role of color terms in the formation of linguistic worldview, as well as conceptualizes and defines the place of the color vocabulary in the cognitive process. Key words: Khanty riddles, basic color terms, color words.